DIGITALISASI POLA PAKAIAN MELALUI CLO3D - Susi Hartanto (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2020)
Moving towards industry 4.0, one of five sectors in Indonesia to be planned as implementation pioneer is textile and clothing industry. Digital competencies have become skill requirement found most in fashion work vacancies. One of common digital method applied in clothing design and production is Clo3D. This article results from a co-creation activity between UPH Product Design, LPK Nadya Jaya, and brand partner (Lovadova); taking Clo3D as a tool to produce 3D patterns, reducing human error, saving time & costs. There are 16 patterns produced, 7 among them are mass-produced. As the result, Clo3D helps in terms of design, revise, simulate clothes in 3D; allowing the clothing business cycle from design to selling a lot faster than traditional process. Key words : Digitalization, Pattern, Clothing, Clo3D